2013
DOI: 10.1001/jamapsychiatry.2013.2163
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Depression During Pregnancy and the Postnatal Period

Abstract: IMPORTANCE Some small studies suggest that maternal postnatal depression is a risk factor for offspring adolescent depression. However, to our knowledge, no large cohort studies have addressed this issue. Furthermore, only 1 small study has examined the association between antenatal depression and later offspring depression. Understanding these associations is important to inform prevention.OBJECTIVE To investigate the hypothesis that there are independent associations between antenatal and postnatal depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
240
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 491 publications
(255 citation statements)
references
References 39 publications
13
240
2
Order By: Relevance
“…This is an important finding and supports the work of Flykt et al (2010), who reported that prenatal depression has a negative effect on attachment between mother and baby with prenatal depressive symptoms having a stronger impact on maternal unresponsiveness with her infant than postnatal depressive symptoms. Depressive symptoms are well known to have a significant impact on a pregnant woman's quality of life (Cohen & Nonacs, 2005) and can impact negatively on her family's health particularly including major depression of her children at age 18 years (Pearson et al, 2013). While there has been some discussion in the literature regarding prenatal depression and subsequent poor attachment in the postnatal period, the linkage between prenatal depression and prenatal attachment has been largely uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important finding and supports the work of Flykt et al (2010), who reported that prenatal depression has a negative effect on attachment between mother and baby with prenatal depressive symptoms having a stronger impact on maternal unresponsiveness with her infant than postnatal depressive symptoms. Depressive symptoms are well known to have a significant impact on a pregnant woman's quality of life (Cohen & Nonacs, 2005) and can impact negatively on her family's health particularly including major depression of her children at age 18 years (Pearson et al, 2013). While there has been some discussion in the literature regarding prenatal depression and subsequent poor attachment in the postnatal period, the linkage between prenatal depression and prenatal attachment has been largely uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term consequences of maternal postnatal depression for the child are profound, in light of the documented link with the emergence of depression [2] and other psychiatric disorders [3] in offspring. Post-partum anxiety is also common, although it has been far less studied than has depression [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to early family risk factors, maternal depressive symptoms (pre‐ and postnatal) are robust and well researched risks for offspring depressive symptoms in adolescence (Pawlby, Hay, Sharp, Waters, & O'Keane, 2009; Pearson et al., 2013) and may act as a common antecedent of the three pathways outlined above (i.e. Irritability Symptoms ; Anxiety/Depressive Symptoms ; and Conduct Problems; Cents et al., 2013; Leis, Heron, Stuart, & Mendelson, 2014; Mars et al., 2012).…”
Section: Introductionmentioning
confidence: 99%